(untitled) (Jurnal Adabiya, 2025)
This study aims to analyze the optimization of digital collection utilization at the West Kalimantan Provincial Library and Archives Service. A qualitative approach was employed, focusing on understanding the perspectives, experiences, and viewpoints of individuals and groups involved in the phenomenon under investigation. Data were collected in textual form through interviews with one librarian responsible for managing electronic resources and two users of the digital collection via the iKalbar application. The findings indicate that the optimization process of digital collection utilization involves several stages, including user needs analysis, collection evaluation based on circulation data, budget allocation from the provincial government (APBD), and the role of staff in collection management and selection. The optimization strategies emphasize the diversification of digital collections, supported by structured collection development policies, collaboration with local publishers, and the implementation of digital library systems. These efforts are designed to enhance information accessibility and improve the quality of services provided to users. Abstrak Penelitian ini bertujuan menganalisis upaya optimalisasi pendayagunaan koleksi digital di Dinas Perpustakaan dan Kearsipan Provinsi Kalimantan Barat. Pendekatan yang digunakan adalah metode kualitatif, dengan fokus pada pemahaman terhadap perspektif, pengalaman, serta pandangan individu maupun kelompok yang terlibat dalam fenomena penelitian. Data diperoleh dalam bentuk teks melalui wawancara dengan seorang pustakawan bidang pengelola bahan elektronik dan dua orang pengguna koleksi digital pada aplikasi iKalbar.Hasil penelitian menunjukkan bahwa tahapan optimalisasi pendayagunaan koleksi digital mencakup analisis kebutuhan pengguna, evaluasi koleksi berdasarkan data peminjaman, pengalokasian dana melalui APBD Provinsi, serta peran staf dalam manajemen dan seleksi koleksi. Strategi optimalisasi difokuskan pada peningkatan keragaman koleksi, yang didukung oleh kebijakan pengembangan koleksi digital secara terstruktur, kerjasama dengan penerbit lokal, serta penerapan teknologi melalui sistem perpustakaan digital. Seluruh langkah tersebut ditujukan untuk memperluas aksesibilitas informasi dan meningkatkan kualitas layanan bagi pengguna.